Advice for prevention from HIV-positive African-American women: 'My story is not just a story'. Issue 5 (4th May 2017) - Robillard, Alyssa; Padi, Akhila; Lewis, Kaleea; Julious, Carmen; Troutman, Jamie
Abstract: Large disparities in HIV incidence, prevalence and mortality exist for African-American women, especially in the southern region of the USA. Based on the culture-centric health promotion model, HIV-positive African American women can use their stories to support primary prevention. The purpose of this study was to document advice from HIV-positive African-American women ( n = 25) to young African-American women, as described in their own cultural narratives collected through qualitative interviews. Content analysis of women's advice identified five common themes revolving broadly around: (1) advice for prevention, (2) support systems for prevention, (3) education, (4) empowerment/self-care and (5) potential barriers to prevention. Advice reflected recommendations based on personal experience and highlighted social determinants linked to HIV, such as stigma, access to education and healthcare, social support, and gender and power dynamics. Women also offered advice for coping with an HIV-positive diagnosis. Communication with parents, family and friends regarding education and social support emerged as an important interpersonal factor for participants, as were interactions with sexual/romantic partners. Stigma, at the community level, was consistently discussed as a hindrance to prevention. Narratives of HIV-positive women as community health agents of change can enhance the effectiveness of HIV prevention interventions for young US African-American women.